Broadband low-frequency vibration attenuation in 3D printed composite meta-lattice sandwich structures. (15th June 2021) - Li, Hao; Hu, Yabin; Huang, Heyuan; Chen, Jianlin; Zhao, Meiying; Li, Bing
Abstract: Achieving superior properties of vibration suppression at low-frequency range, yet with high load-bearing capabilities in lightweight structural designs is still a challenge. In this work, we propose a strategy to realize broadband low-frequency vibration bandgaps by combining the design concepts of locally resonant metamaterials and lightweight lattice-truss-core sandwich structures. Two kinds of meta-lattice sandwich panels consisting of single/double-layer pyramidal truss-cores are designed, and the 3D printing technique of selective laser sintering (SLS) is applied to fabricate the dissipative composite meta-structures. The vibration suppression performance and bandgap generation mechanisms are theoretically, numerically, and experimentally investigated. Remarkable vibration suppression within broadband low-frequency bandgaps, stemming from the coupling between the designed secondary structures and host panels, are numerically and experimentally verified in both time and frequency domains. Equivalent mass-spring models are developed to theoretically predict the vibration attenuation ranges. Bandgap merging effects induced by the damping of the 3D printed meta-structures are further investigated, and remarkably enlarged attenuation bands are experimentally captured. The metamaterial-based lattice sandwich structures pave feasible ways for designing vibration shielding systems with both high functional and mechanical performance.